Additive effects of HLA alleles and innate immune genes determine viral outcome in HCV infection. Issue 5 (4th July 2014) - Fitzmaurice, Karen; Hurst, Jacob; Dring, Megan; Rauch, Andri; McLaren, Paul J; Günthard, Huldrych F; Gardiner, Clair; Klenerman, Paul; ,
Abstract : Background: Chronic HCV infection is a leading cause of liver-related morbidity globally. The innate and adaptive immune responses are thought to be important in determining viral outcomes. Polymorphisms associated with the IFNL3 ( IL28B ) gene are strongly associated with spontaneous clearance and treatment outcomes. Objective: This study investigates the importance of HLA genes in the context of genetic variation associated with the innate immune genes IFNL3 and KIR2DS3 . Design: We assess the collective influence of HLA and innate immune genes on viral outcomes in an Irish cohort of women (n=319) who had been infected from a single source as well as a more heterogeneous cohort (Swiss Cohort, n=461). In the Irish cohort, a number of HLA alleles are associated with different outcomes, and the impact of IFNL3 -linked polymorphisms is profound. Results: Logistic regression was performed on data from the Irish cohort, and indicates that the HLA -A*03 (OR 0.36 (0.15 to 0.89), p=0.027) -B*27 (OR 0.12 (0.03 to 0.45), p=<0.001), -DRB1*01:01 (OR 0.2 (0.07 to 0.61), p=0.005), -DRB1*04:01 (OR 0.31 (0.12 to 0.85, p=0.02) and the CC IFNL3 rs12979860 genotypes (OR 0.1 (0.04 to 0.23), p<0.001) are significantly associated with viral clearance. Furthermore, DQB1*02:01 (OR 4.2 (2.04 to 8.66), p=0.008), KIR2DS3 (OR 4.36 (1.62 to 11.74), p=0.004) and the rs12979860 IFNL3 'T' allele are associated with chronic infection. This study finds no interactive effect between IFNL3 and these Class I and II alleles in relation to viral clearance. There is a clear additive effect, however. Data from the Swiss cohort also confirms independent and additive effects of HLA Class I, II and IFNL3 genes in their prediction of viral outcome. Conclusions: This data supports a critical role for the adaptive immune response in the control of HCV in concert with the innate immune response.